2019
DOI: 10.4103/1673-5374.253535
|View full text |Cite|
|
Sign up to set email alerts
|

Involvement of insulin receptor substrates in cognitive impairment and Alzheimer’s disease

Abstract: Type 2 diabetes—associated with impaired insulin/insulin-like growth factor-1 (IGF1) signaling (IIS)—is a risk factor for cognitive impairment and dementia including Alzheimer’s disease (AD). The insulin receptor substrate (IRS) proteins are major components of IIS, which transmit upstream signals via the insulin receptor and/or IGF1 receptor to multiple intracellular signaling pathways, including AKT/protein kinase B and extracellular-signal-regulated kinase cascades. Of the four IRS proteins in mammals, IRS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…In metabolic imbalance conditions such as obesity, IRS-1 dysregulation leads to insulin resistance in the brain and results in neuropathological problems 54 . Several studies have demonstrated that insulin resistance by IRS-1 and IRS-2 dysregulation in the brain causes onset of neurodegenerative disease and results in cognitive decline 54 , 56 . Serine phosphorylation of IRS-1 elevates amyloid beta accumulation and exacerbates memory deficit in AD brain 57 .…”
Section: Discussionmentioning
confidence: 99%
“…In metabolic imbalance conditions such as obesity, IRS-1 dysregulation leads to insulin resistance in the brain and results in neuropathological problems 54 . Several studies have demonstrated that insulin resistance by IRS-1 and IRS-2 dysregulation in the brain causes onset of neurodegenerative disease and results in cognitive decline 54 , 56 . Serine phosphorylation of IRS-1 elevates amyloid beta accumulation and exacerbates memory deficit in AD brain 57 .…”
Section: Discussionmentioning
confidence: 99%
“…The obvious consequence of this receptor deficit is diabetes [34], the disorder that often occurs also in MPS patients, particularly in MPS III, and in fact, impaired expression of INSR is evident in cells from patients suffering from all MPS III subtypes. However, impaired functions of IGF1 (insulin/insulin-like growth factor) signaling, which includes insulin receptor substrates, have been recognized as a risk factor for dementia and cognitive impairment [35]. Therefore, one might speculate that decreased levels of the insulin receptor may facilitate development of such symptoms in neuronopathic forms of MPS.…”
Section: Discussionmentioning
confidence: 99%
“…This TNF-α counter-insulinic effect, in which the insulin receptor becomes inactivated by increasing the inhibitory phosphorylation threshold of the IRS1, has been broadly described in diabetes (128) and in neurons presenting Tau-pathology and NFT (129). These IRS inhibitory phosphorylations described in AD patients' brains and transgenic mice lead to IR states (34), memory declines, and cognitive impairment (130).…”
Section: Role Of Inflammationmentioning
confidence: 97%